Antisense-Oligonucleotide Mediated Exon Skipping in Activin-Receptor-Like Kinase 2: Inhibiting the Receptor That Is Overactive in Fibrodysplasia Ossificans Progressiva - Shi, SongTing (Public Library of Science, 2013)
Fibrodysplasia ossificans progressiva (FOP) is a rare heritable disease characterized by progressive heterotopic ossification of connective tissues, for which there is presently no definite treatment. A recurrent activating mutation (c.617G→A; R206H) of activin receptor-like kinase 2 (ACVR1/ALK2), a BMP type I receptor, has been shown as the main cause of FOP. This mutation constitutively activates the BMP signaling pathway and initiates the formation of heterotopic bone. In this study, we have designed antisense oligonucleotides (AONs) to knockdown mouse ALK2 expression by means of exon skipping. The ALK2 AON could induce exon skipping in cells, which was accompanied by decreased ALK2 mRNA levels and impaired BMP signaling. In addition, the ALK2 AON potentiated muscle differentiation and repressed BMP6-induced osteoblast differentiation. Our results therefore provide a potential therapeutic approach for the treatment of FOP disease by reducing the excessive ALK2 activity in FOP patients.